2006
DOI: 10.1159/000090520
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cytokine Induction and Removal of Complement Products with Synthetic Hemodialysis Membranes

Abstract: The increasing use of high-flux membranes for hemodialysis (HD) has raised concerns that these membranes may confer a higher risk of exposure to cytokine-inducing, bacterial substances (CIS) in the dialysate. Several studies, however, reported higher transfer of CIS through low-flux cellulosic than high-flux synthetic membranes. This surprising paradox was explained by adsorption of CIS to certain high-flux membranes. In order to investigate flux and membrane type independently, we studied two synthetic Polyfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Hence, intraoperative dialysis has become our standard of care during liver transplant surgery for patients who require dialysis preoperatively to manage both volume and acidosis. At our institution, hemodialysis is performed with biocompatible membranes, which theoretically reduce protein oxidation and complement activation, thereby providing a more stable procedure [47][48][49]. Dialysis membranes effectively remove molecules below a molecular weight of 1,500 Da.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, intraoperative dialysis has become our standard of care during liver transplant surgery for patients who require dialysis preoperatively to manage both volume and acidosis. At our institution, hemodialysis is performed with biocompatible membranes, which theoretically reduce protein oxidation and complement activation, thereby providing a more stable procedure [47][48][49]. Dialysis membranes effectively remove molecules below a molecular weight of 1,500 Da.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the transfer of bacterial contamination products through MCO and HCO membranes was only evaluated in closed in vitro dialysis cir-cuits [28][29][30][31][32] . Using such in vitro investigations, it could be demonstrated that increasing pore size does not result in higher cross-contamination towards the blood side of lipopolysaccharide (LPS) isolated from Escherichia coli O55:B5 [33] .…”
Section: Why Do We Need Studies On Cross-contamination Of Bacterial Pmentioning
confidence: 99%
“…Another aspect is the removal of cytokines and other inflammatory markers (lipopolysaccharide fragments, granulocyte inhibitory proteins 1 and 2, IL-1, TNF-) and complement factors (C3a, C5a) by the hemodialysis procedure as well as the adsorption of substances to the hydrophobic high-flux membrane (e.g. factor D) (Clark et al 1999;Schindler et al 2006). Dialysis can reduce leukocyte-endothelial interactions and impair transmigration (Thylen et al 1997).…”
Section: Patients On Hemodialysismentioning
confidence: 99%
“…In patients on hemodialysis with cuprophane or polysulfone membranes, a significantly higher serum level of MCP-1 is seen compared with healthy subjects both before and after the hemodialysis session, independent of the membrane used (Jacobson et al 2000;Thylen et al 2000). Biocompatibility of dialysis membranes probably plays an important role in determining leukocyte function in patients on hemodialysis (Himmelfarb et al 1991;Himmelfarb et al 1993;Hernandez et al 2004;Schindler et al 2006). High serum levels of cytokines and chemokines have been observed in patients on hemodialysis with modified cellulose membranes (Descamps-Latscha 1993; Pawlak et al 2004;Muniz-Junqueira et al 2005).…”
Section: Patients On Hemodialysismentioning
confidence: 99%
See 1 more Smart Citation